SIMULATION OF THE MOBILE OBJECTS IDENTIFICATION PROCESSES IN THE SUPPLY CHAINS - Stepanov, Pavel V.; Zakharov, Valerii V.; Markov, Vladimir P.; Andrianov, Yurii S. (Journal of Applied Engineering Science, 2025)
The paper considers the problem of choosing the optimal combination of identification technologies for a class of cyber-physical systems controlling technological (micro-logistics) processes, the specificity of which does not allow using the same identification method at all technological stages. The formal statement of the problem is presented. Criteria, constraints and conditions of search for optimal combinations of technologies are defined. The solution of the problem is considered on the example of the control system of mobile equipment turnover. The simulation model created for generation of full space of admissible variants of combinations of identification technologies, calculation of parameters, modeling of technological process execution and search of quasi-optimal solution is described. The model structure, main modules and functions are disclosed. The simulation model presented in this article generates the full space of admissible variants of identification technology combinations, performs parameter calculations, simulates technological process execution, and identifies quasi-optimal solutions. The model's structure, including its key modules and functions, is also described. The space of admissible configurations obtained from the simulation is analyzed. The results of the optimal solution search are presented, along with their dependence on the model's parameters and constraints.
Keywords: micro-logistics processes monitoring, optimisation methods, automation of logistics process control